Implementing an AIK-Integrated Snakes-and-Ladders Game to Support Foundational Literacy and Numeracy Among Children in Orphanage - Royani Puspandoyo; Sandha Soemantri; Mukayat Al Amin; Imtihanatul Ma'isyatuts Tsalitsah; Ngatma'in Ngatma'in; Bagus Khansakumara; Devi Aprilia; Eka Indah Wuriani; Farahdibah Ade Makantika; Faridah Sal Sabillah; Ganesha Gistha Annafi; Nur Fauziatul Azkiyak (Khidmatuna : Jurnal Pengabdian Masyarakat, 2026)
Children in orphanage often learn in mixed-age groups with markedly different levels of foundational literacy and numeracy, while access to interactive, low-technology learning media may be limited. This community-based study examined the implementation of Mentari Snakes and Ladders, a floor-sized educational game integrating differentiated reading, writing, and arithmetic tasks with Al-Islam and Kemuhammadiyahan (AIK) values. Twelve elementary-school-aged children at a Muhammadiyah orphanage institution in Surabaya participated in five 90-minute sessions in May 2026. Data were drawn from needs-assessment observations and interviews, initial diagnostic tasks, written products, challenge-card records, structured behavioral observations, reflection journals, and a final individual assessment. Quantitative evidence was summarized descriptively, while qualitative records were organized thematically around feasibility, participation, differentiated support, academic practice, and values-related behavior. The program was feasible in the available space and enabled children from Grades 1-6 to participate in a common activity through tiered challenge cards and graduated prompts. The number meeting the specified reading criterion increased from 2 to 7 of 12, simple-sentence writing from 1 to 6, and two-digit arithmetic from 3 to 8. Consistent observations of shiddiq, amanah, ta’awun, and takaful also increased. The findings indicate that the game offers a context-responsive mechanism for combining foundational learning, movement, peer assistance, and values-based reflection. Because the initial and final assessments were not identical and the study had no comparison group, the results constitute preliminary descriptive evidence rather than causal proof of effectiveness.